IMPACT OF COMPUTER VISION SYNDROME ON HEALTH OF COMPUTER USAGE BANK EMPLOYEE - RAMZAN, SHAHID; IRFAN, MOHAMMAD (IJRDO -Journal of Computer Science Engineering, 2016)
The computer has become a common item in today’s society. Nearly 60 million people suffer from CVS globally and a million new cases occur each year. The aim to investigate the awareness and knowledge about Computer vision syndrome (CVS) among Bank employees. The sample of this study consisted 50 Bank employees. Both males and females bank employees from private and public sector were selected. The Sample was randomly selected. The ages of Employees were 26 to 48. Self Prepared Questionnaire, Expert Reviewed and Pilot were used to access the Objective. The results indicated that impact of Computer vision syndrome on the health of human being who used the prolonged computer usage. The investigator found a lot of the remedies and relieves from Computer vision syndrome were as ; Blink more often (12-18/minute),Take breaks frequently (20-20-20 rule) after every 20 minutes look at distant object at least 20 feet away for 20 seconds, Modify work place, Exercise & stretch eyes, Monitor display quality-choose a setting in which refresh rate and resolution both are high, Adjust the brightness of computer screen, Exercise even when sitting- stand up, move about or exercise arms, leg, back, neck, and shoulders frequently.